Application of Modern Collective Ijtihād Approach in Islamic Banking: Analysis of AAOIFI's Juristic Methodology - Azeem Abdullah; Ahmad Che Yaacob; Hussin Salamon (Universiti Sains Islam Malaysia, 2024)
Ulum Islamiyyah, Volume 36 Issue 2 Page (89–96)